Association of plasma endothelin-1 with blood pressure progression among Blacks: The Jackson Heart Study - Kaze, Arnaud D.; Gao, Xiang; Musani, Solomon K.; Bidulescu, Aurelian; Bertoni, Alain G.; Abdalla, Marwah; Echouffo-Tcheugui, Justin B. (The American heart journal, 2022)
Despite pathophysiological links between endothelin (ET)-1 and hypertension in Black adults, there is no population-based data appraising the association of plasma ET-1 with longitudinal blood pressure (BP) changes in Blacks. We analyzed data from 1197 Jackson Heart Study participants without hypertension (mean age 47.8 years [SD: 12.0]; 64.2% women), with plasma ET-1 available at the baseline examination (2000-2004). Poisson regression with robust variance was used to generate risk ratios (RRs) and 95% confidence intervals (CIs) of BP progression (an increase by ≥1 BP category based on the 2017 American College of Cardiology/American Heart Association classification) and incident hypertension (BP ≥ 130/80 mm Hg or use of antihypertensive medication) at follow-up (2005-2008 or 2009-2013). Over a median follow-up of 7 years (range: 4-11), 71.2% (n = 854) progressed to a higher BP stage and 64.6% (n = 773) developed hypertension. After adjusting for possible confounders, each unit increment in baseline log (ET-1) was associated with higher risks of BP progression (RR 1.15 [95% CI 1.03-1.29], P = .016) and incident hypertension (RR 1.15 [95% CI 1.01-1.31], P = .032). Compared to those in the lowest ET-1 quartile, participants in the highest quartile had significantly higher risks of BP progression (RR 1.20 [95% CI 1.05-1.37], P = .007) and incident hypertension (RR 1.16 [95% CI 1.00-1.36], P = .052). In a large, community-based sample of African Americans, higher plasma ET-1 concentrations were associated with higher risks of BP progression and incident hypertension.